Effects of Telemedicine and mHealth on Systolic Blood Pressure Management in Stroke Patients: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Lv, Meina; Wu, Tingting; Jiang, Shaojun; Chen, Wenjun; Zhang, Jinhua (JMIR Publications, 2021)
BackgroundStroke is a common, harmful disease with high recurrence and mortality rates. Uncontrolled blood pressure is an important and changeable risk factor for stroke recurrence. Telemedicine and mobile health (mHealth) interventions may have the potential to facilitate the control of blood pressure among stroke survivors, but their effect has not been established. ObjectiveThis systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to estimate the effects of telemedicine and mHealth interventions on the control of systolic blood pressure among stroke survivors. MethodsThe research literature published up to June 28, 2020, and consisting of RCTs related to telemedicine and mHealth interventions was searched in PubMed, EMBASE, Web of Science, and the Cochrane Library. The Cochrane risk of bias tool (RoB 2.0) was used to evaluate the quality of the studies. The Cochran Q test and I2 statistic were used to assess heterogeneity. Data were meta-analyzed using a random-effects model. Mean difference (MD) with 95% CI and 95% prediction interval (PI) were calculated. ResultsIn total, 9 RCTs with a total sample size of 1583 stroke survivors met the inclusion criteria. Compared with the usual care, telemedicine and mHealth had a significantly greater impact on the control of systolic blood pressure (MD -5.49; 95% CI -7.87 to -3.10; P<.001; 95% PI -10.46 to -0.51). A subgroup analysis showed that the intervention mode of telephone plus SMS text messaging (MD -9.09; 95% CI -12.71 to -5.46; P<.001) or only telephone (MD -4.34; 95% CI -6.55 to -2.13; P<.001; 95% PI -7.24 to -1.45) had a greater impact on the control of systolic blood pressure than usual care. Among the stroke survivors with an intervention interval ≤1 week (MD -6.51; 95% CI -9.36 to -3.66; P<.001; 95% PI -12.91 to -0.10) or a baseline systolic blood pressure ≥140 mm Hg (MD -6.15; 95% CI -9.44 to -2.86; P<.001; 95% PI -13.55 to 1.26), the control of systolic blood pressure using telemedicine and mHealth was better than that of usual care. ConclusionsIn general, telemedicine and mHealth reduced the systolic blood pressure of stroke survivors by an average of 5.49 mm Hg compared with usual care. Telemedicine and mHealth are a relatively new intervention mode with potential applications for the control of systolic blood pressure among stroke survivors, especially those with hypertensive stroke.